Penerapan Komunikasi Partisipasi Pada Program Stunting MBKM Bina Desa di Desa Puuk Kaway XVI - Putra, Ilhamna Mazal; Juliani, Reni (Lok Seva: Journal of Contemporary Community Service, 2023)
Implementation of the MBKM Bina Desa Stunting Program was carried out in Puuk Village, Kaway XVI, West Aceh. The service program carried out is the practice of making and supplementary feeding, and socialization of Healthy Lifestyle (PHS) both orally and in writing in the form of poster design. oral and written in the form of poster design. Activities This service was carried out on August 25, 2022, with a target audience of 21 people. in the community as many as 21 people. The service model carried out is door-to-door, which is based on the stages of planning, implementation, and evaluation. to evaluation. The result of this service is that the community gets direction related to the criteria for children and toddlers who experience symptoms of stunting. The community has active involvement in program implementation. This starts from community participation in assessments, and program alternatives to program implementation.  Therefore, the application of participatory communication participatory communication through the Stunting MKBM bina Puuk Village, Kaway XVI, West Aceh has been implemented with planning.